The Effect of Foot Bath Therapy With Warm Water and Salt on Blood Pressure in Hypertension Patients - Nugraheni, Lisa Asri; Saelan, Saelan; Ardiani, Nurul Devi (Pena Medika : Jurnal Kesehatan, 2023)
Hypertension or high blood pressure is a condition of abnormally increased blood pressure in the arteries (Harnani & Axmalia, 2021). Treatment of hypertension could be performed using non-pharmacological measures or naturally at a relatively low cost. Non-pharmacological treatments are therapeutic such as acupressure therapy, herbal therapy, aromatherapy, and hydrotherapy of warm water foot soaks (Santoso, et al 2021).  Foot bath therapy with warm water is a type of hydrotherapy to improve blood circulation, relax tight muscles, and provides warmness to the body. It is beneficial for blood pressure reduction therapy in hypertension sufferers. The research adopted a quantitative study using a pre-experimental design with a one-group pre-post-test design. The sampling used a non-probability sampling technique with 39 respondents. Data analysis operated the Wilcoxon test with a p-value = 0.000 (p-value <0.05). Thus, Ho was rejected, and Ha was accepted. The results revealed that the blood pressure in the pre-foot bath therapy of warm water and salt presented averaged 140 – 159 mmHg of 21 respondents (53.8%). The post-action of foot bath therapy of warm water with salt presented an average blood pressure of 140-159 mmHg of 21 respondents (53.8%). The Wilcoxon test concluded that foot bath therapy with warm water and salt had affected blood pressure in hypertensive patients in Joho Village of Mojolaban District.